2012
DOI: 10.1186/1475-2840-11-78
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of different glucose abnormalities in patients with acute myocardial infarction treated invasively

Abstract: BackgroundDiabetes (DM) deteriorates the prognosis in patients with coronary heart disease. However, the prognostic value of different glucose abnormalities (GA) other than DM in subjects with acute myocardial infarction (AMI) treated invasively remains unclear.AimsTo assess the incidence and impact of GA on clinical outcomes in AMI patients treated with percutaneous coronary intervention (PCI).MethodsA single-center, prospective registry encompassed 2733 consecutive AMI subjects treated with PCI. In all in-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
(43 reference statements)
0
36
0
1
Order By: Relevance
“…The authors emphasized that the main finding of their study was that IGT negatively affected the treatment outcomes and that the long-term prognosis of patients with IGT was similar to those with DM. The analysis of particular MACE which occurred during long-term observation showed that there were no significant differences between patients with normal glucose tolerance and IFG, IGT, or DM with respect to recurrent AMI, percutaneous coronary intervention, coronary artery by-pass grafting or stroke [17]. The adverse role of IGT in AMI patients was also confirmed in a study by George et al in which 42% of the study population was treated invasively [18].…”
Section: Value Of Oral Glucose Tolerance Test In Acute Phase Of Acutementioning
confidence: 70%
See 2 more Smart Citations
“…The authors emphasized that the main finding of their study was that IGT negatively affected the treatment outcomes and that the long-term prognosis of patients with IGT was similar to those with DM. The analysis of particular MACE which occurred during long-term observation showed that there were no significant differences between patients with normal glucose tolerance and IFG, IGT, or DM with respect to recurrent AMI, percutaneous coronary intervention, coronary artery by-pass grafting or stroke [17]. The adverse role of IGT in AMI patients was also confirmed in a study by George et al in which 42% of the study population was treated invasively [18].…”
Section: Value Of Oral Glucose Tolerance Test In Acute Phase Of Acutementioning
confidence: 70%
“…Impaired fasting glycemia (isolated or coexisting with impaired glucose tolerance) was observed in 10-15%, but it was reported infrequently. In patients with coronary artery disease, 2h-PG has a similar diagnostic and prognostic usefulness as in other populations [12,13,14,15,16,17,18]. Tamita et al classified AMI patients with respect to fasting glucose as subjects with normal or impaired fasting glycemia and showed that there were no significant differences in the major adverse cardiovascular events (MACE) between those groups.…”
Section: Value Of Oral Glucose Tolerance Test In Acute Phase Of Acutementioning
confidence: 99%
See 1 more Smart Citation
“…Сахарный диабет, по данным ряда авторов [24][25][26], встречается у 17-34% больных с острым коронарным синдромом. Принято считать, что данное заболевание существен-но усугубляет течение ОИМ [27].…”
Section: актуальные вопросы кардиологииunclassified
“…Newly detected diabetes mellitus (DM) or impaired glucose tolerance were associated with similar mortality to pre-hospital diabetes [5]. In stable patients after AMI, derangements in glucose metabolism defined at hospital discharge were shown to be transient, persistent, unchanged, or newly detected [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%